RZYMSKA KONCEPCJA WŁASNOŚCI W KULTURZE PRAWNEJ EUROPY - Rozwadowski, Władysław (Zeszyty Prawnicze, 2016)
ROMAN CONCEPT OF OWNERSHIP IN THE EUROPEAN LEGAL CULTURE Summary Ownership is a fundamental subjective right as well as a basis of freedom. The Roman concept of property was very broad, at first uniform and then differentiating between the dominium ex iure Quiritium and other forms of ownership (bonitary and in the provinces). According to Justinian’s constitution from 530 AD, ownership was to become uniform again. The common opinion that Roman jurists did not reach a precise definitione of ownership seems too far-reaching. It is possible that such a definitione existed but was not included in the Digest. Four basic rights of the owner were listed by the glossators and then Bartolus de Saxoferrato defined ownership as ius de re corporali perfecte disponendi, nisi lege prohibeatur.